The effect of melatonin and 6-Benzylaminopurine application on the post-harvest quality of cut roses (Rosa x alba) - Putri, Azizah Tiara; Mubarok, Syariful; Budiarto, Rahmat (Universitas Padjadjaran, 2025)
Roses are known as a high-value commodity frequently used in various important events. However, they are susceptible to postharvest quality deterioration, which can affect their vase life and appearance. In this study, roses with a blooming stage of approximately 25–50% were immersed in melatonin and 6-benzylaminopurine (BAP) solutions at different concentrations. This research aims to analyze the effect of melatonin and BAP application on the freshness of cut roses. The parameters observed included flower vase life, flower wilting angle, increase in flower diameter, fresh weight, solution uptake, and chlorophyll content. The results showed that melatonin and BAP, applied individually or in combination, effectively extended the freshness of cut roses by up to eight days by maintaining solution uptake, flower quality, and chlorophyll content. This study provides new insights for farmers and researchers in improving the quality and longevity of cut roses through the use of plant hormones, particularly cytokinin.